(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Indian constitution is dedicated to the establishment of rule of law with right to equality for man and women. The idea of equality is specifically incorporated in the Indian constitution’s many clauses. The constitution not only guarantees women’s equality, but it also authorizes the state to take particular steps to ensure women’s liberation. India is a signatory to a number of international agreements and conventions aimed at ensuring equal rights for women. In this sense, the most important instrument that India has ratified is the 1993 Convention on the Elimination of All Forms of Discrimination Against Women.[1]